2015
DOI: 10.2174/1573403x10666140902143020
|View full text |Cite
|
Sign up to set email alerts
|

How does Chronic Atrial Fibrillation Influence Mortality in the Modern Treatment Era?

Abstract: Atrial fibrillation (AF) continues to impose a significant burden upon healthcare resources. A sustained increase in the ageing population and better survival from conditions such as ischaemic heart disease have ensured that both the incidence and prevalence of AF continue to increase significantly. AF can lead to complications such as embolism and heart failure and these acting in concert with its associated co-morbidities portend increased mortality risk. Whilst some studies suggest that the mortality risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 88 publications
0
38
0
Order By: Relevance
“…[ 2 ] While there are multiple estimates, the yearly incidence in the US is expected to grow, for example, from 1.2 million cases in 2010 to 2.6 million cases in 2030 and upwards of 6–12 million cases by 2050. [ 1 , 3 ] It is associated with increased morbidity and mortality[ 4 ] and diminished quality of life. [ 5 ] AF is associated with structural heart disease, but it may also occur in a structurally normal heart.…”
mentioning
confidence: 99%
“…[ 2 ] While there are multiple estimates, the yearly incidence in the US is expected to grow, for example, from 1.2 million cases in 2010 to 2.6 million cases in 2030 and upwards of 6–12 million cases by 2050. [ 1 , 3 ] It is associated with increased morbidity and mortality[ 4 ] and diminished quality of life. [ 5 ] AF is associated with structural heart disease, but it may also occur in a structurally normal heart.…”
mentioning
confidence: 99%
“…A prospective study done in the University of Vienna reported that the incidence of cardiac arrhythmias in surgical and medical intensive care units were 15.7% and 19.7 %, respectively [3] . AF is considered one of the most commonly sustained arrhythmias in clinical practice [16] . In the current study, none of the patients admitted into the CCU with AF had any mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Th is outlines the denotative morbidity accompanying AF and therefore explains the consequence of increased duration of stay in the CCU. It also off ers a clarifi cation for any associated mortality, as some studies now show that the mortality risk of AF is more likely attributed to the entailing co-morbidities rather that the conduction abnormality alone [16] . Th e ability to correctly assess patients and stratify them based on the risk for prolonged and complicated hospitalization indubitably guides the expectations of patients, clinicians, administrators and even reimbursement policies [18] .…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy about whether the excess mortality observed in patients with AF aged 85 is directly due to AF . While some studies suggest that the mortality risk of AF is really due to the associated co‐morbidities and complications such as embolism or heart failure rather than AF itself, some other studies advocate the role of the side effects of the therapeutic strategies used for treating AF (anti‐arrhythmic drugs, bleeding side effects due to anti‐coagulants, etc.)…”
Section: Discussionmentioning
confidence: 99%